Feasibility determination of low-head hydroelectric power development at existing sites. Final report - Polonsky, R. (Bethlehem Mink Farm, Littleton, OH (USA), 1979)
This report contains the feasibility study, economic analysis, and information relevant to reactivation of the dam in Bethelehem, NH. It outlines a plan of development which calls for sale of the power to a local utility for the first few years of the project and then predominately on-site use of the power in an innovative plan for controlled-environment agriculture. The economic analyses indicate that reactivation of the dam would be a successful venture based on the present market value of 4.5 cents/kWh. The success of the second phase in the dam's use rests on the increasing financial attractiveness of locally grown produce in a state that currently imports over 90% of its food and is experiencing the spiraling costs of food, energy, and inflation. The best-suited turbine package for the site is an Ossberger 750-kW unit which would provide 4,014,000 kWh per year with a plant factor of 61%. The total capital costs of the project are $827,935.